(untitled) (JURNAL ADMINISTRASI PUBLIK, 2021)
Limitation of infrastructure, such as providing access to economic centers, access to plantations and the availability of clean water, became the obstacle of the rural developing. This research uses a qualitative approach. Data obtained from interviews, observations, and documentation. The data obtained were then analyzed use data reduction techniques, data models, and verification. The focus of this study refer to five indicators of the effectiveness of implementing the rural infrastructure development program, namely the right policy, the right implementation, the right target, the right environment, and the right process. Right on policy, government policies regarding existing problems such as construction of production roads, provide the clean water and productive businesses can be resolved. Appropriate implementation, the implementation of rural infrastructure development was carried out in stages or gradually. Right on target, the target of rural infrastructure development is to realize increased access for the poor and in this achievement the government has designated Kayuuwi 1 as the target group by involving the community. Environmentally appropriate, assessment by institutions involved in implementation and involve the community as a group that related institutions and the community alike positively assess the PPIP program implemented in Kayuuwi 1. Appropriate process, the process starts from planning, implementation, and supervision, to decision making. The existing process is working and PPIP in Kayuuwi 1, West Kawangkoan is proceeding according to the existing process. Keyword : programs effectiveness, infrastructure, rural development